Experience and perception of social mobility: A cross-country test of the self-serving bias - Nina Weber (Luxembourg Income Study (LIS), 2020)
Perceptions of social mobility in society are one of the most important determinants of individuals' preferences for redistribution and tolerance for economic inequalities. What shapes these perceptions is however so far little understood. In this paper, I propose and empirically test a behavioural model of social mobility perceptions based on the self-serving bias, using the ISSP Social Inequality Cumulative. The self-serving bias states that people blame external circumstances for their failures and take excessive credit for their successes. The results of my analysis indicate, in line with the expectations of the self-serving bias, that personal experiences with social mobility only influence people's perceptions of societal mobility if the experiences were negative or stagnating. Conversely, those who experienced positive mobility overestimate their personal contribution and, therefore, do not extrapolate from their experience onto perceptions of society at large. Instead, their perceptions are primarily related to their political orientation, with those towards the right of the political spectrum being more optimistic about social mobility and those towards the left being more pessimistic.
Keywords: D31; D72; D91; 330; social mobility; perceptions; self-serving bias; procedural fairness; political orientation